Requirement for the Murine Zinc Finger Protein ZFR in Perigastrulation Growth and Survival - Meagher, Madeleine J. (American Society for Microbiology, 2001)
The transition from preimplantation to postimplantation development leads to the initiation of complex cellular differentiation and morphogenetic movements, a dramatic decrease in cell cycle length, and a commensurate increase in the size of the embryo. Accompanying these changes is the need for the transfer of nutrients from the mother to the embryo and the elaboration of sophisticated genetic networks that monitor genomic integrity and the homeostatic control of cellular growth, differentiation, and programmed cell death. To determine the function of the murine zinc finger protein ZFR in these events, we generated mice carrying a null mutation in the gene encoding it. Homozygous mutant embryos form normal-appearing blastocysts that implant and initiate the process of gastrulation. Mutant embryos form mesoderm but they are delayed in their development and fail to form normal anterior embryonic structures. Loss of ZFR function leads to both an increase in programmed cell death and a decrease in mitotic index, especially in the region of the distal tip of the embryonic ectoderm. Mutant embryos also have an apparent reduction in apical vacuoles in the columnar visceral endoderm cells in the extraembryonic region. Together, these cellular phenotypes lead to a dramatic development delay and embryonic death by 8 to 9 days of gestation, which are independent of p53 function.